Factors Affecting the Tendency of International Students to Pursue Study in Universiti Malaysia Sabah - Jupiter, Herlina; Wani Othman, Irma; Mohd Suki, Norazah (International Journal of Psychosocial Rehabilitation, 2019)
This study discusses the tendency of international students to pursue their studies at Universiti Malaysia Sabah (UMS) and the factors involved in their selection. The enrolment of international students in higher institutions nowadays has become a significant element to be recognized as a world-class study center. Therefore, various efforts and strategies need to be designed to increase the number of international students. Understanding the factors affecting the decision of an international student can give an idea to the university in order to implement the appropriate strategy and simultaneously attract them to enroll in the program, resulting in positive effects for the university itself. There are two main objectives of this study, which are firstly to identify the factors that influence international students to study abroad and secondly, to evaluate the Universiti Malaysia Sabah (UMS) selection factor as a destination for international students. The methodology of this study is using a qualitative research method and a case study type. A total of 20 respondents from various nationalities were randomly selected and interviewed in depth to get the required appropriate data. Based on the conceptual framework of Suh Li Phang (2013), the factors influencing university selection by international students were divided into three significant categories: (i) (i) communication, (ii) location, and (iii) social. The author analyzed the causes for international students to choose UMS and found three newness as a contribution to the body of knowledge. Hence, this information should be adapted to develop a better plan of international student enrolment strategy in UMS and to ensure the sustainability of the Malaysian higher education sector.